1994
DOI: 10.1159/000236669
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Traditional Chinese Herbal Therapy in Atopic Eczema

Abstract: A traditional Chinese herbal therapy (Zemaphyte®) for the treatment of atopic eczema (AE) is currently being assessed. This review attempts to highlight its success in patients who are recalcitrant to Western forms of treatment and the rationale behind its use. The herbal preparation is a mixture of 10 herbs with some known pharmacological agents and actions. The concept of such a complex mixture in clinical treatment is anathema to Western medicine but acceptable in traditional Chinese medicine. As this forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 22 publications
(27 reference statements)
0
13
0
Order By: Relevance
“…More and better designed trials and possibly a systematic review of literature on TCP available in the Western world are needed. Wang [98] Chen [94] without name [93] Shen [92] Shi [67] Jiang [62] Wu [105] Hu [106] Liao [107] Fang [108] Li [68] Drabaek [64] Drabaek [63] Li [78] Hsieh [77] Worm [49] Ramgolam [38] Fung [48] Armstrong [47] Koo [46] Sheehan [44] Sheehan [43] Latchmann [42] Sheehan [40] Sheehan [41] Atherton [39] Batey [25] Akbar [24] Chen [14] Hirayama [13] Caceres [80] Scaglione [72] (continued) Chen [86] Liang [83] Hale [82] Chen [20] Tatsuta [19] Hou [17] Lin [6] Lin [12] Charuwichitratana [71] Sangkitporn [69] Davis [33] Hirata [32] Ding [30] Wang [28] Ramgolam …”
Section: Resultsmentioning
confidence: 99%
“…More and better designed trials and possibly a systematic review of literature on TCP available in the Western world are needed. Wang [98] Chen [94] without name [93] Shen [92] Shi [67] Jiang [62] Wu [105] Hu [106] Liao [107] Fang [108] Li [68] Drabaek [64] Drabaek [63] Li [78] Hsieh [77] Worm [49] Ramgolam [38] Fung [48] Armstrong [47] Koo [46] Sheehan [44] Sheehan [43] Latchmann [42] Sheehan [40] Sheehan [41] Atherton [39] Batey [25] Akbar [24] Chen [14] Hirayama [13] Caceres [80] Scaglione [72] (continued) Chen [86] Liang [83] Hale [82] Chen [20] Tatsuta [19] Hou [17] Lin [6] Lin [12] Charuwichitratana [71] Sangkitporn [69] Davis [33] Hirata [32] Ding [30] Wang [28] Ramgolam …”
Section: Resultsmentioning
confidence: 99%
“…In studies of interleukin (IL) 4-induced CD23 expression on monocytes, there appeared to be a reduction of the CD23 expression when the cells were exposed to the aqueous herb extracts. 2,49 Another study examined immunologic markers for T cells, macrophages, Langerhans cells, and low-affinity and highaffinity IgE receptors in biopsy specimens of lesional skin treated with Zemophyte compared with biopsy specimens of nonlesional skin. 50 The investigators found clinical improvement similar to that seen in the studies described above and also found that the improvement was associated with statistically significant reduction in CD23 antigen-presenting cells.…”
Section: Chinese Herbal Medicinementioning
confidence: 99%
“…Treatment is usually a mixture of herbs, massage, and acupuncture. 2 In Western medicine, herbal therapy began as folk medicine. In the United States, it began in the colonial days, when Florida, Tampa. homemade botanicals were provided by the women in the home.…”
mentioning
confidence: 99%
“…Many studies in Europe were carried out in recent years to evaluate TCM treatments for specific conditions with variable results. In the UK, a daily decoction containing 10 herbs was found to be more effective than placebo in improving patients with chronic atopic dermatitis in erythema, surface damage, patients' subjective feeling on itching and sleep in a randomized, double-blind placebo-controlled trial [22,23]. In Nerthlands, the effectiveness of Chinese herbal medicine (CHM) integrated with TCM diagnosis was confirmed for the treatment of postmenopausal symptoms when compared with hormone replacement therapy (HRT) or placebo in a randomized placebo-controlled trial [24].…”
Section: Effectiveness Of Traditional Chinese Medicinementioning
confidence: 99%